An Analysis of Linguistic Features Used in Business News of BBC and The Guardian Website - Alda Rizky Nur Afida Abdullah; Mariana Ulfah Hoesny; Nugrahaningtyas Fatma Anyassari (UPT P2M Politeknik Negeri Malang, 2025)
This research analyzed and classified linguistic features found in 16 business news from BBC and The Guardian in January 2024 edition. The business news consist of 300 words approximately. Adapting qualitative method and descriptive analysis to collect the data, the research adopted David Crystal’s theory, which specifically divided linguistic features into five categories, namely lexical, grammatical, discourse, orthographic, and graphic features. The findings of this research mentioned that there are 4 linguistic features identified: lexical, grammatical, discourse, and orthographic. Moreover, the linguistic features mostly found is grammatical features in branch of conjunctions, which have crucial role in establishing coherence and clarity in news writing to make communication effectively. Adopting a case study approach, this research provides the insight and understanding how linguistic features influence the context of business news.